Antagonistic muscle prefatigue weakens the functional corticomuscular coupling during isometric elbow extension contraction. Issue 5 (25th March 2020) - Wang, Lejun; Xie, Zihang; Lu, Aiyun; Lu, Tianfeng; Zhang, Shengnian; Zheng, Fanhui; Niu, Wenxin
Abstract : Objective: During muscle fatigue, acute changes in the interaction between the sensorimotor cortex and peripheral neurons have been widely studied. However, it is still unclear about the effect of antagonist muscle prefatigue on corticomuscular coupling and central modulation. The purpose of this study was to investigate the changes in the magnitude of electroencephalogram-electromyography (EEG-EMG) coherence and phase synchronization index (PSI) induced by antagonistic muscle prefatigue. Methods: Twelve young male volunteers conducted a 30-s long, nonfatiguing isometric elbow extension with a target force level of 20% maximum voluntary contraction (MVC) before and after a fatiguing sustained elbow flexion contraction at 20% MVC until task failure. Coherence and PSI between the EEG recorded over the sensorimotor cortex and the surface EMG of the triceps brachii (TB) muscle were quantified for the pre- and post-fatigue elbow extension contractions. Results: Coherence and PSI in the gamma frequency band (35–60 Hz) were found significantly decreased in the postfatigue elbow extension contraction than the prefatigue contraction. The power of the EEG in the beta and gamma band were significantly increased, while the EMG power showed no significant changes when the antagonistic muscle was prefatigued. PSI in the gamma frequency band between the EMG of the TB muscle and the EEG were found significantly decreased during postfatigue elbow extension contraction compared with prefatigue contraction. Conclusion: Antagonistic muscle prefatigue led to significantly lower gamma band corticomuscular coherence and phase coupling during an isometric elbow extension position task. The lower corticomuscular coupling may indicate a central modulation mechanism of antagonist muscle prefatigue that related to decreased descending common drive or joint instability compensation modulation mechanism.